DIPILIH DAN MEMILIH, KESETARAN POLITIK BAGI KELOMPOK PENYANDANG DISABILITAS PADA PEMILU DEMOKRASI DI SUMATERA BARAT - Soraya Oktarina (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
Every human has the same rights in the political contestation of a country, he has the right to be elected and also to vote. Disability groups as part of Indonesian citizens have the right to be actively involved in political activities. Undang-undang No. 7 tahun 2017 is the basis of reference for groups of persons with disabilities to apply to be elected in general elections, but reality shows low perception and trust towards groups of persons with disabilities, the unavailability of quotas and opportunities from supporting political parties. In West Sumatra, the level of political participation of the disabled group is still low. In Sumatera Barat regional head selection in 2020 , the average political participation rate for persons with disabilities only reached 35 percent. This study used descriptive qualitative method. This paper tries to analyze what political rights and needs of groups of persons with disabilities are in implementing the People's Democratic Party and what obstacles occur in efforts to fulfill the political rights of groups of persons with disabilities in West Sumatra. This is necessary, bearing in mind that the next general election will be held again. There is a need to understand the need for political rights of persons with disabilities in order to encourage an increase in the interest and participation of people with disabilities in determining the fate of the Indonesian nation in the future